Frequency of Metabolic Syndrome in Patients with Hepatitis C Virus Infection - Khan, Hafiz Abdul Basit; Saeed, Samina; Khalid, Talha; Rafiq, Sidrah Muhammad; Ahmed, Numan; Khan, Abdullah (Biological and Clinical Sciences Research Journal, 2025)
Hepatitis C virus (HCV) infection is a major global health burden, traditionally associated with chronic liver disease. Objective: To determine the frequency of metabolic syndrome in patients with chronic hepatitis C virus infection and assess its association with demographic and clinical variables. Methods: This cross-sectional observational study was conducted at the Department of General Medicine, AIMC/Jinnah Hospital, Lahore, from March 2025 to May 2025. A total of 220 patients aged 20–60 years with confirmed HCV infection were enrolled using non-probability consecutive sampling. Demographic data, clinical examination findings, and laboratory results, including fasting blood glucose, triglycerides, HDL cholesterol, and blood pressure, were recorded. Results: The mean age of patients was 42.7 ± 10.2 years; 124 (56.4%) were male and 96 (43.6%) were female. Metabolic syndrome was identified in 49 patients (22.3%). Significant associations were found between MetS and age ≥45 years (p = 0.04) as well as BMI ≥25 kg/m² (p < 0.001). No significant association was observed between MetS and duration of HCV infection (p = 0.12). Conclusion: It is concluded that metabolic syndrome is a frequent comorbidity in patients with chronic HCV infection, particularly among older and overweight individuals. Routine screening for metabolic risk factors in HCV patients is recommended to facilitate early intervention and reduce associated cardiovascular and hepatic complications.